Tren Penelitian Global tentang Akuntansi Manajemen Strategis dan Kinerja UMKM: Analisis Bibliometrik - Dwi Utami (Jurnal Akuntansi Nommensen, 2026)
Strategic Management Accounting (SMA) has become an important instrument for improving Micro, Small, and Medium Enterprises (MSME) performance in the digital era. The increasing adoption of digital technologies has encouraged researchers to explore the role of SMA in supporting competitiveness, decision-making, and business sustainability. This study aims to identify global research trends, influential publications, collaboration networks, and emerging themes related to Strategic Management Accounting and MSME performance. This study employed a bibliometric analysis approach using articles indexed in Scopus between 2014 and 2024. Data were analyzed using VOSviewer to visualize co-authorship, keyword co-occurrence, and citation networks. The findings indicate a significant increase in publications related to SMA and MSME performance during the last five years. The dominant research themes include digital transformation, financial performance, sustainability, competitive advantage, and innovation capability. The analysis also reveals that developed countries dominate the publication landscape, while research collaboration among developing countries remains limited. Strategic Management Accounting has become a growing research area with substantial contributions to MSME performance in the digital era. Future studies are recommended to explore empirical evidence from developing countries and integrate sustainability and digital innovation.